1997
DOI: 10.1111/j.1440-1754.1997.tb01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of school entry immunization certificates

Abstract: Objective: To compare the immunization certificate submission rate for kindergarten school children on the Central Coast of New South Wales for 1994 and 1995; to contact individual parents of children with incomplete or missing immunization certificates by issuing a personalised immunization reminder letter, and measuring their response. Methodology: Seventy Central Coast schools were surveyed. Immunization documentation for 41 77 kindergarten enrolments in 1995 were assessed. Children with incomplete or unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In a similar KAP study in India 76% of mothers were aware of the use and the necessity to save immunization cards [12]. An investigation in Australia suggested that specifically targeting parents through schools could be an effective way of increasing immunization certificate submission [23]. Legislation requiring parents to provide proof of immunization for children entering school has been found to be effective in improving immunization coverage rate and reducing the incidence of vaccine-preventable disease in a number of countries [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar KAP study in India 76% of mothers were aware of the use and the necessity to save immunization cards [12]. An investigation in Australia suggested that specifically targeting parents through schools could be an effective way of increasing immunization certificate submission [23]. Legislation requiring parents to provide proof of immunization for children entering school has been found to be effective in improving immunization coverage rate and reducing the incidence of vaccine-preventable disease in a number of countries [23].…”
Section: Discussionmentioning
confidence: 99%